Optimal monetary policy in a new Keynesian model with animal spirits and financial markets - Matthias Lengnick; Hans-Werner Wohltmann (Kiel University, Department of Economics, 2014)
This paper relates to the literature on macro-finance-interaction models. We modify the boundedly rational New Keynesian model of De Grauwe (2010a) using a completely microfounded IS equation, and combine it with the agent-based financial market model of Westerhoff (2008). For this purpose we derive four interactive channels between the financial and real sector where two channels are strictly microfounded. We analyze the impact of the different channels on economic stability and derive optimal (simple) monetary policy rules. We find that coefficients of optimal simple Taylor rules do not significantly change if financial market stabilization becomes part of the central bank's objective function. Additionally, we show that rule-based, backward-looking monetary policy creates huge instabilities if expectations are boundedly rational.
Keywords: E03; E5; G02; 330; agent-based financial markets; New Keynesian macroeconomics; microfoundation; optimal monetary policy; unconventional monetary policy